2011
DOI: 10.1002/cjg2.1670
|View full text |Cite
|
Sign up to set email alerts
|

East Asian Precipitation Pattern: Competition Between Monsoon and Transient Eddies

Abstract: This paper aims at investigating climate integrated column moisture transport (MT in brief hereafter) over the troposphere for 1971~2000 and the relationship between the MT divergence and seasonal precipitation in East Asia. The result made from ERA‐40 shows that the spatial pattern of the precipitation is approximately coincided with large‐scale MT divergence. A further decomposition manifests that the monthly‐wind moisture transport (MMT) is the dominant role for seasonal divergence patterns. The MMT converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The anomalous transient eddy term in summer is smaller than winter because transient wave activity weakens rapidly from spring to summer (Nakamura 1992). In all four modes, the anomalous transient eddies have the opposite phase by supplying or blocking moisture over the boundary region of the mean flow and their role is smaller than the moisture flux convergence (Zhang et al 2011). In other words, the transient eddy divergence (convergence) is observed to influence a decrease (an increase) in rainfall (Zhang et al 2011).…”
Section: Moisture Budget Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The anomalous transient eddy term in summer is smaller than winter because transient wave activity weakens rapidly from spring to summer (Nakamura 1992). In all four modes, the anomalous transient eddies have the opposite phase by supplying or blocking moisture over the boundary region of the mean flow and their role is smaller than the moisture flux convergence (Zhang et al 2011). In other words, the transient eddy divergence (convergence) is observed to influence a decrease (an increase) in rainfall (Zhang et al 2011).…”
Section: Moisture Budget Analysismentioning
confidence: 93%
“…The moisture budget studies have been widely known over the recent decade. For example, Zhang et al (2011) tried to show the moisture divergence by dividing into the monthly-wind moisture transport (MMT) and transient eddy moisture transport (EMT) divergence. They revealed that the MMT represents strong moisture convergence in the EASM region, while the EMT divergence has the opposite effect on the MMT.…”
Section: Introductionmentioning
confidence: 99%
“…Lower SE regions are distributed in areas near the boundaries, such as the South China Sea and western Pacific Ocean in the South, Siberia and the Mongolian Plateau in the North and Southwest, and the Tibetan Plateau in the west. In relation to the monsoons in China, a southward marine monsoon in summer and a northward continental monsoon in winter dominate the WVS (Sheng, ; Zhang, ). Marine WV primarily originates from the western Pacific and the South China Sea in the South and from the Bay of Bengal in the Southwest.…”
Section: Discussionmentioning
confidence: 99%
“…Marine WV primarily originates from the western Pacific and the South China Sea in the South and from the Bay of Bengal in the Southwest. The continental sources are primarily Siberia in the North and the Caspian Sea and Southwest Tibetan Plateau in the west (Zhang, ). By comparing the entropy distribution and WVS regions, each major WVS region corresponds to a lower SE region (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation